Anthracene biodegradation capacity of newly isolated rhizospheric bacteria Bacillus cereus S13. - Nadia Bibi; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Badshah Islam; Farooq Shah; Muhammad Aaqil Khan; In-Jung Lee (PLoS ONE)
Biodegradation of hazardous pollutants is of immense importance for maintaining a clean environment. However, the concentration of such contaminants/pollutants can be minimized with the help of microorganisms that has the ability to degrade the toxic pollutants into non-toxic metabolites. In the current study, 23 bacterial isolates were purified from the rhizospheric soil of Sysimbrium irio, growing as a wild plant in the vicinity of gas filling stations in Peshawar city. The isolated strains were initially screened on solid nutrient agar and further purified by culturing it on anthracene amended mineral media (PNR). The bacterial growth and anthracene disappearance were observed by calculating optical density (OD). The isolates showed a concentration-dependent growth on anthracene amended PNR media at 30°C and pH7. Also, an increase in bacterial OD from 0.351 to 1.80 with increased shaking speed was noticed. On the contrary, alternate carbon sources (glucose, fructose, sucrose) or nitrogen sources (KNO3, NaNO3, NH4NO3 and CaNO3) posed inhibitory effect on bacterial growth during anthracene degradation. The recorded efficiency of anthracene degradation by the selected bacterial isolate (1.4×1023 CFUmL-1 and 1.80 OD) was 82.29%, after 120 h of incubation. The anthracene was degraded to 9, 10, dihydroxy-anthracene and anthraquinone, detected through GC-MS. The efficient bacterial isolate was identified as S13, a new strain of Bacillus cereus, using 16S rRNA analysis, showing 98% homology. The isolated bacterial strain S13 may be used as a potential tool for bioremediation of toxic hydrocarbons and to keep the environment free from PAH pollutants.